Music therapy was noninferior to verbal standard treatment of traumatized refugees in mental health care: Results from a randomized clinical trial. Issue 1 (1st January 2021) - Beck, B. D.; Meyer, S. L.; Simonsen, E.; Søgaard, U.; Petersen, I.; Arnfred, S. M. H.; Tellier, T.; Moe, T.
ABSTRACT: Background : Many people with refugee backgrounds suffer from trauma-related complex social and psychological problems, and compliance with standard psychological treatment tends to be low. More culturally adaptable treatment options seem to be needed. Objective : We aimed to investigate whether the music therapy method: 'trauma-focused music and imagery' (tr-MI), characterized by a particular focus on arousal and affect regulation, would be equally effective as the standard psychological talk therapies for ameliorating trauma symptoms in Danish refugees. Methods : A pragmatic, noninferiority, parallel, randomized controlled trial with six-month follow-up was carried out at three clinics for refugees in the public mental health services of the Psychiatry (DK). Seventy-four adults diagnosed with posttraumatic stress disorder (PTSD) were allocated to either music therapy sessions (tr-MI, N = 39) or psychological treatment as usual (TAU, N = 35). Western classical music, new age music, and music from the participants' own national culture were used to generate inner imagery, following a phased treatment protocol. Homework entailed listening to music. The primary outcome was the measurement of trauma symptoms by the Harvard Trauma Questionnaire, section IV (HTQ-IV); secondary measures were somatoform and psychoform dissociation (DSS-20), SDQ-20), attachment (RAAS), and well-being (WHO-5). Treatment effects reflected by primary and secondary measures were estimated using linear mixed models. Results : Tr-MI was noninferior to TAU (mean difference at follow-up HTQ-IV: 0.14, CI (−0.10; 0.38), with a − 0.3 noninferiority margin). A high dropout rate of 40% occurred in the TAU group, compared to 5% in the music therapy group. Secondary measures generated small to medium effect sizes in both groups, with significant medium effect sizes for well-being and psychoform dissociation at follow-up in tr-MI. Conclusions : Tr-MI is an innovative form of psychological treatment in refugee mental health services. Trials comparing music therapy to standardized therapy are needed to substantiate the evidence base for tr-MI therapy. HIGHLIGHTS: Music therapy was shown to be no less effective than standard psychological treatment regarding the decrease of posttraumatic stress disorder symptoms in a randomized clinical trial with 74 adult traumatized refugees. Good retainment and significant changes in well-being and dissociation during six-month follow-up were found in music therapy.